Wanders or residents: ethnography along the Way of Saint James of Compostella - Gasparo, Costanza (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2021)
The focus of the research is the Way of Saint James. Foncebadón is a small ghost village that has begun to attract pilgrims daily; while Santiago de Compostela is the Walk final city. I used two techniques: participant observation and interviews. Both techniques have been used to elaborate some pilgrims and workers identity profiles. Participant observation was used to observe social interactions in natural contexts, biographical interviews to recreate pilgrim’s biographical paths and witness interviews to analyse the vision of some local workers referring to some aspects of the way. The figure of pilgrim is now close to that of the tourist. The inhabitants of Foncebadón consider the way as an opportunity for cultural exchange; while a revaluation of the city tourist identity seems to be necessary to keep together paths of mutual enrichment between pilgrims and inhabitants.